5x-2(x-3)=2(x+5) si x(x+5)=2(x+2)
Răspunsuri la întrebare
Răspuns de
1
5x-2x+6=2x+10 x²+5x=2x+4
5x-2x-2x=10-6 x²+5x-2x=4
x=4 x²+3x=4
x²+3x-4=0
x²+4x-x-4=0
x(x+4)-(x+4)=0
(x+4)(x-1)=0⇒x+4=0 si x-1=0
x=0-4 x=0+1
x=-4 x=1
5x-2x-2x=10-6 x²+5x-2x=4
x=4 x²+3x=4
x²+3x-4=0
x²+4x-x-4=0
x(x+4)-(x+4)=0
(x+4)(x-1)=0⇒x+4=0 si x-1=0
x=0-4 x=0+1
x=-4 x=1
deny261:
multumesc mult
Alte întrebări interesante
Biologie,
9 ani în urmă
Limba română,
9 ani în urmă
Franceza,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă